2007
DOI: 10.1002/cmr.b.20099
|View full text |Cite
|
Sign up to set email alerts
|

Design and performance of a DNP prepolarizer coupled to a rodent MRI scanner

Abstract: For most of the last forty years, the techniques of Dynamic Nuclear Polarization (DNP) have been confined to particle-physics laboratories building polarized targets, but recently it has been shown that samples similar to a solid target can be transformed into room temperature liquid solutions while retaining a high nuclear polarization. This method of ' 'hyperpolarization' ' is of interest in NMR/MRI/MRS. We describe a 3.35 T DNP/9.4 T MRI installation based on a continuous-flow cryostat, using a standard wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
249
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(259 citation statements)
references
References 29 publications
10
249
0
Order By: Relevance
“…A total volume of 300 μL of this solution was inserted, in the form of 10 μL frozen beads (prepared in liquid nitrogen), into a 5 T custom-designed DNP polarizer prefilled with liquid helium [38]. The 13 C nuclei were dynamically polarized for 2 h at 1.15 K. Following a previously described automated process [39], the beads were rapidly dissolved in 6 mL of pressurized, heated D 2 O and the resulting solution was transferred within 2 s into a separator/infusion pump located inside an actively shielded 31-cm diameter horizontal bore 9.4 T magnet (Magnex Scientific, Abingdon, UK) [40]. The separator/infusion pump was prefilled with 0.6 mL of phosphate buffered saline and heparin.…”
Section: Sample Preparation and Hyperpolarization Protocolmentioning
confidence: 99%
“…A total volume of 300 μL of this solution was inserted, in the form of 10 μL frozen beads (prepared in liquid nitrogen), into a 5 T custom-designed DNP polarizer prefilled with liquid helium [38]. The 13 C nuclei were dynamically polarized for 2 h at 1.15 K. Following a previously described automated process [39], the beads were rapidly dissolved in 6 mL of pressurized, heated D 2 O and the resulting solution was transferred within 2 s into a separator/infusion pump located inside an actively shielded 31-cm diameter horizontal bore 9.4 T magnet (Magnex Scientific, Abingdon, UK) [40]. The separator/infusion pump was prefilled with 0.6 mL of phosphate buffered saline and heparin.…”
Section: Sample Preparation and Hyperpolarization Protocolmentioning
confidence: 99%
“…This solution was polarized at 3.35 T and 1.2 K using a custombuilt polarizer described by Comment et al 35,48 The output power of the 94 GHz microwave source was set to 30 mW. After dissolution into 5 ml of superheated D 2 O pressurized at 10 bars, the solution was automatically transferred within 4 s to a phase separator/infusion pump placed in the bore of the 9.4 T system positioned approximately 4 m away from the DNP polarizer.…”
Section: Experimental Dissolution Dnpmentioning
confidence: 99%
“…pyruvate, acetate and bicarbonate) have been the most promising candidates. [32][33][34][35] Previous studies have shown the utility of this technique for detecting in vivo tumors in animal models 36,37 and very low contrast agent concentrations. 38 To date, besides optically polarized 3 He and 129 Xe, 39 6 Li is the only hyperpolarized nucleus besides 13 C that has been reported to be detected in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Frozen beads were placed in a home-built prepolarizer 12 and irradiated with 30 mW of microwave power at 94 GHz for 3 h at 1.2 K and 3.35 T. The sample was rapidly dissolved in 5 mL of D 2 O (at ca. 190°C and 12 bar) to a final choline concentration of 50 ( 5 mM.…”
mentioning
confidence: 99%